POSITION OF PERSONAL GUARANTEE IN PROVIDING GUARANTEE TO CREDITORS FOR CREDIT FACILITIES OBTAINED BY DEBTORS RELATED TO POSTPONEMENT OF DEBT PAYMENT OBLIGATIONS (PKPU) (Case Study of the Decision of the Central Jakarta Commercial District Court Number: 2 - Annisa Rizkika Chairiza Nasution; Tan Kamello; Suprayitno (PT. Radja Intercontinental Publishing, 2024)
This study is expected to introduce an investigation into Indonesian Regulations regarding the responsibility and implementation of PKPU with the aim of solving and providing solutions. This research method uses a normative research type. The data collection technique used in this study is library research. The results of the study explain First, Individual Guarantors should not be positioned as Respondents in PKPU. Second, the legal consequences of Guarantors who have released their privileges are considered to have bound themselves together with the main debtor, but the context of the release of privileges is only for confiscation in bankruptcy, not for PKPU. Third, Analysis of the legal considerations of the judge in the Decision of the Central Jakarta Commercial District Court Number: 212 / Pdt.Sus-PKPU / 2019 / PN.Niaga.Jkt.Pst is to consider in terms of the formal requirements of the PKPU Application that there is one requirement that is not met, namely PKPU which cannot be proven simply because the withdrawal of the guarantee to the Respondent is wrong and contradicts Article 254 of the Bankruptcy and PKPU Laws.